Las TIC's como herramienta en el proceso de enseñanza aprendizaje. - Jácome Pruna, Mayra Beatriz (2018)
The information and communication technologies (ICTs) have become significant elements inherent to the development in all life’s spheres. Education is not beyond these realities because this field embraces an unlimited universe of possibilities as learning resources to be likely extended to a higher users’ number at different scenarios in order to socialize knowledge. Our country has been consistent with the imperative demand for the ICTs development and implementation, which cover all the educational levels and become very important in the higher education universalization. The education technologies functions are at the same time their fundamental impacts such as source: information, communication channel, cognitive and processing instrument, among others. For this reason, it has mentioned imposes new roles on the leading players of the formative process and brings new challenges for the future professionals. Also, It is responsible in the formation institutions since the latter will have to deal with technical matters, specialized formation, information protection and other aspects derived from the ICT expansion. The ICTs’ use has strengthened and dimensioned since the emergence in the health care field. These technologies allow introducing new paradigms in the medical education like student-centered education, self-learning and knowledge management, which have changed the professor historical role. The ICTs have facilitated the creation of pedagogic model-based virtual educational spaces that can assure learning by using innovative strategies.